An Overview of Ensembl - Birney, Ewan; Andrews, T. Daniel; Bevan, Paul; Caccamo, Mario; Chen, Yuan; Clarke, Laura; Coates, Guy; Cuff, James; Curwen, Val; Cutts, Tim; Down, Thomas; Eyras, Eduardo; et al.

(untitled) (Genome Research, 2004)
Ensembl (http://www.ensembl.org/) is a bioinformatics project to organize biological information around the sequences of large genomes. It is a comprehensive source of stable automatic annotation of individual genomes, and of the synteny and orthology relationships between them. It is also a framework for integration of any biological data that can be mapped onto features derived from the genomic sequence. Ensembl is available as an interactive Web site, a set of flat files, and as a complete, portable open source software system for handling genomes. All data are provided without restriction, and code is freely available. Ensembl's aims are to continue to “widen” this biological integration to include other model organisms relevant to understanding human biology as they become available; to “deepen” this integration to provide an ever more seamless linkage between equivalent components in different species; and to provide further classification of functional elements in the genome that have been previously elusive.